ALL I NEED IS SUNLIGHT: OVIDIAN METAMORPHOSIS AND THE POSTHUMAN SUBJECT IN HAN KANG’STHE VEGETARIAN - Theodora Tsimpouki (Journal of Posthuman Studies, 2021)
The language of arboreal metamorphosis in Han Kang’s The Vegetarian not only invokes the Ovidian myth of Daphne and Apollo but also establishes a post-anthropocentric perspective according to which the irreducible material and symbolic connections between humans and other entities are brought to light. Drawing on the Derridean concept of carnophallogocentrism, on one hand, and on posthuman feminist scholarship, on the other, this article argues that the protagonist’s gradual release from her bond to Anthropos to embrace forms of plant life highlights feminist posthumanism’s attempt to explore the intricate relationships of human beings with each other and other species outside the parameters of anthropocentrism.